Analysis on affecting factors of magnetorheological finishing. Issue 1 (January 2021) - Hao, Lanfang; Liu, Zhongling; Li, Shixu; Zhu, Ruiyu; Zhu, Xuli
Abstract: A magnetorheological finishing experimental device was designed and fabricated to explore influencing factors during polishing process. The device consists of the subsystems of mechanical transmission, workpiece clamp, magnetorheological fluid circulation and magnetic excitation. Magnetorheological fluids of different carbonyl iron volume ratio were prepared to research the effects with different workpiece speeds, polishing wheel speeds during magnetorheological finishing. The material of the workpiece is K9 glass. Experiment results show that the material removal rate increases with the workpiece speed and the speed of the polishing wheel. The increasing of volume ratio of carbonyl iron can also increase the material removal rate when the volume ratio is low, but the removal rate decreases when the volume ratio of the carbonyl iron powder reaches high value.